2013
DOI: 10.1097/qco.0b013e3283638104
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in low-income and middle-income countries

Abstract: Purpose of review Human brucellosis is a neglected, underrecognized infection of widespread geographic distribution. It causes acute febrile illness and a potentially debilitating chronic infection in humans, and livestock infection has substantial socioeconomic impact. This review describes new information regarding the epidemiology of brucellosis in the developing world and advances in diagnosis and treatment. Recent findings The highest recorded incidence of human brucellosis occurs in the Middle East and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
181
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 103 publications
1
181
0
8
Order By: Relevance
“…the consumption of unpasteurised milk and dairy products, and/or animal husbandry activities) plays a very important role in its diagnosis. (8) However, patient history cannot help to distinguish infected from non-infected persons. While the majority of the patients diagnosed with brucellosis in the present study had a history of consuming unpasteurised milk and dairy products, and/or animal husbandry activities, 48 (29.3%) of the 164 patients did not report any risk factors, thereby raising the suspicion that supermarket products may have been prepared in inappropriate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…the consumption of unpasteurised milk and dairy products, and/or animal husbandry activities) plays a very important role in its diagnosis. (8) However, patient history cannot help to distinguish infected from non-infected persons. While the majority of the patients diagnosed with brucellosis in the present study had a history of consuming unpasteurised milk and dairy products, and/or animal husbandry activities, 48 (29.3%) of the 164 patients did not report any risk factors, thereby raising the suspicion that supermarket products may have been prepared in inappropriate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many indicators that suggest that prevention strategies are not only feasible, but would positively impact human health and production. 6,23 For example, a cost-effectiveness study on mass vaccination of livestock found that by allocating costs to all sectors this strategy would benefit everyone. 24 Also, well-implemented programs of milk pasteurization in informally marketed products can effectively reduce human transmission.…”
Section: Discussionmentioning
confidence: 99%
“…2 In Mexico, HB is endemic with a reported annual incidence of 25.7 cases per 100 000 person-years. 6 The largest report to date analyzed 67 982 sera of healthy individuals (one to 98 years old) obtained from the National Seroepidemiolgy Survey. This study estimated a national mean seroprevalence of 3.42%, and found an association with gender (women), but not with occupation.…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis continues to be a significant zoonosis worldwide, with epidemiologic data suggesting that it remains a significant problem in many countries, and increasing or re-emerging in others [1]. Humans are effectively dead-end hosts and persistence of brucellosis requires maintenance in susceptible reservoir hosts.…”
Section: Introductionmentioning
confidence: 99%